Adjuvant chemotherapy for resected triple negative breast cancer patients: A network meta-analysis. (February 2023) - Petrelli, Fausto; Bertaglia, Valentina; Parati, Maria Chiara; Borgonovo, Karen; De Silva, Pushpamali; Luciani, Andrea; Novello, Silvia; Scartozzi, Mario; Emens, Leisha A.; Solinas, Cinzia
Abstract: The current standard of care for resected early-stage triple negative breast cancer (TNBC) patients who did not receive systemic preoperative therapy is adjuvant anthracycline- and taxane-based chemotherapy (CT). A network meta-analysis (NMA) of randomized controlled trials (phase III) enrolling patients with resected stage I-III TNBC comparing adjuvant regimens was performed. Overall survival (OS) and disease-free survival (DFS) data were extracted. A total of 27 phase III clinical trials were selected including 15, 242 TNBC patients. This NMA showed an OS benefit from the incorporation of capecitabine into classic anthracycline/taxane-based combinations compared to anthracyclines with or without taxanes alone. Highlights: The current adjuvant therapy for resected early-stage triple negative breast cancer is adjuvant chemotherapy. A network meta-analysis (NMA) of randomized controlled trials was performed. A total of 27 phase III clinical trials were selected including 15, 242 TNBC patients. Anthracycline- and taxane-plus capecitabine-based CT resulted in better OS than other regimens. Similarly capecitabine-based triplets and the carboplatin/paclitaxel doublet ranked the best for DFS.